2016
DOI: 10.1016/j.ygyno.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Progestins inhibit calcitriol-induced CYP24A1 and synergistically inhibit ovarian cancer cell viability: An opportunity for chemoprevention

Abstract: We show for the first time that progestins and vitamin D synergistically reduce cell viability and induce apoptosis in ovarian cells and that progestins PR-dependently inhibit CAL-induced CYP24A1, thus extending CAL activity. The combination of progestins and vitamin D deserves further consideration as a strategy for inhibiting ovarian carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
2
22
1
Order By: Relevance
“…In previous studies, we have shown that progesterone-calcitriol combination has cytotoxic and pro-apoptotic effects against ovarian and endometrial cancer cells in vitro [22][23][24][25]. In the present in vitro study, progesterone-calcitriol combination synergistically enhanced the anti-proliferative, cytotoxic, and pro-apoptotic effects of DDP compared to those cells treated with a single agent.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In previous studies, we have shown that progesterone-calcitriol combination has cytotoxic and pro-apoptotic effects against ovarian and endometrial cancer cells in vitro [22][23][24][25]. In the present in vitro study, progesterone-calcitriol combination synergistically enhanced the anti-proliferative, cytotoxic, and pro-apoptotic effects of DDP compared to those cells treated with a single agent.…”
Section: Discussionsupporting
confidence: 61%
“…Earlier studies have shown that a combination of progesterone-calcitriol treatment synergistically inhibited the growth of endometrial and ovarian cancer cell lines [22][23][24][25]. To date, whether the progesterone-calcitriol combination can effectively promote efficacies of anticancer chemotherapeutics has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that progesterone and calcitriol inhibit ovarian and endometrial cancer growth through caspase-3 activation, induction of G 0 –G 1 cell-cycle arrest, downregulation of TGF-β, MMP-9 and MMP-2 signaling [ 27 , 28 , 29 , 30 ]. In the present study, we found a moderate (10–20%) decrease of MT1-MMP activity in calcitriol treated cells compared to vehicle treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we have shown that combining progesterone with calcitriol have synergistic inhibitory effects on growth of endometrial and ovarian cancer cells [ 27 30 ]. The aim of the present study is to evaluate whether the combination of progesterone with calcitriol exerted antitumor effects on invasion and metastasis of human endometrial cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Solar ultraviolet-B (UVB) irradiation increases the serum vitamin D level in humans [21,22], suggesting that vitamin D may have protective effect against ovarian cancer. Calcitriol (1,25-dihydroxycholecaldiferol, 1,25(OH) 2 D 3 ), the active form of vitamin D, exerts antineoplastic effects in colorectal cancer [23], prostate cancer [24,25], ovarian cancer [26,27] and breast cancer [28]. A Phase II trial of the combinational therapy with calcitriol and anti-inflammatory drugs [29,30] (such as naproxen and dexamethasone) showed antitumor activities in prostate cancer patients with safety and well tolerance.…”
Section: Introductionmentioning
confidence: 99%